Aligning Expectations and Perceptions: Analyzing Library User Satisfaction in Higher Education in Rural Philippines - Seno-Sanoria, Maricel (Journal of Interdisciplinary Perspectives, 2025)
In today’s rapidly evolving academic environment, libraries must continually adapt to meet the changing needs of their users to remain practical and relevant. Libraries are vital to academic life, providing key resources and services that support the learning and teaching needs of students and faculty. This study examines the alignment between user expectations and perceptions of academic library services in rural Philippine state universities, with a focus on frontline services, information resources, and facilities. Recognizing academic libraries as pivotal to student learning and research, the research addresses the underexplored context of rural institutions, where infrastructural and digital inequities pose significant challenges. Guided by a gap analysis framework and employing quantitative methods, data were gathered through a validated Likert-scale survey administered to 346 randomly selected undergraduate students who utilized library services during the academic year. Descriptive and inferential statistical analyses revealed that while users hold high expectations, many services meet or exceed these expectations, notably in staff support, digital service provision, resource relevance, and communication channels. However, critical gaps emerged in borrowing policies, user education and training, technology availability, and physical facilities, highlighting areas for targeted improvement. The findings underscore the importance of context-specific assessments in enhancing library service quality and user satisfaction, thereby contributing to academic success and equitable access within rural higher education settings. This study offers valuable insights for library management, educators, and policymakers to develop responsive, user-centered strategies that align with evolving educational needs and support continuous service innovation across the Philippine higher education landscape.